Analysis of brainwave dominant after HR intervention using EEG for theta and delta state / Norhaslinda Ismail - Ismail, Norhaslinda (2010)
This paper presents analysis of brainwave dominant after horizontal rotation (HR) intervention using electroencephalogram (EEG). First, this research will be conducted by distributing questionnaire to the 40 samples. Then, EEG signals were captured from them that before and after they going through three sessions of HR using two-channel bipolar connection in a controlled environment. Basically, brainwave has four categories which are Alpha, Beta, Theta and Delta. However, this research will only focus on theta and delta. Paired T-test analysis was used and graphs were plotted to show the correlation between the left and right brainwave before and after HR intervention to verify brainwave dominant. It was observed that, after HR for all three sessions the brainwave was balanced but most of them have right dominant.